Manajemen Ruang Terbuka Publik di Kota Samarinda - Zefni Kanzu (Syntax Corporation Indonesia, 2023)
The lack of attention to the importance of Green Open Spaces, insufficient policies and strategies for Urban Spatial Planning as outlined in the City Development Plan, and the lack of oversight in the implementation of urban development have led to a decrease in both the quantity and quality of Green Open Spaces. This is due to conflicts of interest with other types of development, with a preference for industrial and commercial sectors as they are seen to generate more employment opportunities (economic factor), without considering the existing environmental aspects. Additionally, development aims to enhance efficiency and effectiveness in providing public facilities for community needs. Samarinda City strives to achieve the mandated 30% proportion of Green Open Spaces, as stipulated by Law Number 26 of 2007 concerning Spatial Planning. However, due to limited available land, the city government faces challenges in designating suitable spaces for Green Open Spaces. The diminishing identity of Green Open Space areas, combined with ongoing urban development, has resulted in impacts such as the emergence of slum-like impressions, obstructed views, and limited public accessibility, particularly along the riverbanks, which are central points of focus in this study. The objective of this research is to formulate strategies to enhance the effectiveness of green open spaces in Samarinda City. The targets are to identify factors influencing the ineffectiveness of green open spaces and to formulate strategies for improving their effectiveness. For both of these objectives, a descriptive-qualitative analysis will be conducted, which will serve as a reference for formulating strategies to enhance the effectiveness of green open spaces and to understand the factors influencing their ineffectiveness in Samarinda City.